(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Indonesia consists of hundreds of tribe, one of them which is dwelled in the Bukit Duabelas Biosphere Reserve in Jambi, the Kubu tribe (Anak Dalam tribe). Their daily living is very dependent upon the native surrounding. The results of interviews during the research with the figure or tribe-head (Temenggung) and Kubu tribe member, indicated that at least 193 plant species recorded. These plants were used as food (69 species), construction materials (42 species), medicines (39 species), house hold utensils (11 species), dye (1 species), latex producing plants (5 species), for ritual materials (9 species), and others (15 species). How the customs and habits of Kubu tribe people manage and use of plant resources were discussed in this paper. Â© 2003 Jurusan Biologi FMIPA UNS Surakarta Keywords: Ethnobotany, Kubu tribe, Bukit Duabelas Biosphere Reserve, Jambi